2003
DOI: 10.1128/jcm.41.3.1245-1247.2003
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Human Immunodeficiency Virus p7-p1-p6 gag Gene in Drug-Naive and Pretreated Patients

Abstract: Resistance to antiretroviral agents often results from mutations within the human immunodeficiency virus (HIV) pol gene. Moreover, insertions within the p6 gag-pol region have recently been found to be involved with resistance to nucleoside analogs. Overall, we found that 21% of 156 specimens collected from HIV-infected individuals (17.6% from 74 drug-naive patients and 24.4% from 82 pretreated patients) harbored these insertions. Insertions around the KQE (Lys-Gln-Glu) motif were found in 12.2% of the pretrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 18 publications
(11 reference statements)
2
21
2
Order By: Relevance
“…One study has shown that these insertions occurred with equal frequency in HIV-1 isolates from both drug-naive and drug-experienced patients (13), whereas other studies have shown that they are seen more frequently in HIV-1 from drug-experienced individuals (28). In the Los Alamos database (23), no insertions identical to those in the present study have been reported, although a number of other insertions have been seen.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…One study has shown that these insertions occurred with equal frequency in HIV-1 isolates from both drug-naive and drug-experienced patients (13), whereas other studies have shown that they are seen more frequently in HIV-1 from drug-experienced individuals (28). In the Los Alamos database (23), no insertions identical to those in the present study have been reported, although a number of other insertions have been seen.…”
Section: Discussioncontrasting
confidence: 49%
“…Although various inserts have been reported to occur around the p6 Gag's PTAP motif (13,28), their exact amino acid sequences have not been well documented, and their frequency and role have been controversial. One study has shown that these insertions occurred with equal frequency in HIV-1 isolates from both drug-naive and drug-experienced patients (13), whereas other studies have shown that they are seen more frequently in HIV-1 from drug-experienced individuals (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, the basis for such duplications has not been clearly defined. Some groups have reported no association between the frequency of PTAP duplications and cART (43,44), whereas other studies have documented a significant increase in the frequency of PTAP duplications in patients on therapy (45)(46)(47). Tamiya et al reported that amino acid insertions near Gag cleavage sites, including PTAP duplications, increased processing by PR mutants bearing PI resistance changes; however, the role of PIs in this phenomenon was not investigated (48).…”
mentioning
confidence: 94%
“…PR genes were then resequenced to confirm mutations. To check for possible adaptation of PR cleavage sites with a particular PR genotype (4,5,16), the sites located in the gag region were amplified with primers P24INF (5Ј-GTCCAAA ATGCGAACCCAGATTGTAA-3Ј) and PNL43R (5Ј-CGCTG CCAAAGAGTGATCTGAGGGAA-3Ј). The gag fragment had 528 nucleotides and contained CA/p2, p2/NC, NC/p1, p1/TFP, and p1/p6 cleavage sites.…”
mentioning
confidence: 99%